PENGARUH TINGKAT KONFLIK TERHADAP PRESTASI KERJA PERAWAT RUMAH SAKIT (Kasus Rumah Sakit Jiwa Tampan Pekanbaru) - Putri, Dewi Karina; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Conflict is a situation that is experienced, felt and can be created. Conflict can impact - positively influence which is useful for performance enhancement. Work performance is a measure measure of success or the success of the work during the work had done. This study discusses the influence of the level of conflict (as seen from the communication within the organization, organizational structure and personality differences in values) on job performance of nurses (consisting of the quality of work, quality of work, toughness and attitude).This study aims to determine the effect of the conflict on the level of work performance of nurses. This research was conducted at the Mental Hospital Tampan Pekanbaru. Subjects in this study were nurses working in the Mental Hospital Tampan Pekanbaru with census sampling technique as much as 88 nurses. Collecting data using a questionnaire. The data analysis method used in this study descriptive analysis and chi square test (χ2). The research results indicate there is significant effect between the level of conflict with the work performance of nurses on RSJ Tampan Pekanbaru. From the calculation results show that the obtained χ2 count is greater than χ2 table is 10.36> 9.488.Key word: level of conflict, job performance.